2020
DOI: 10.1159/000506689
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Body Mass Index and Waist Circumference on the Incidence of Hypertension in a Community-Based Chinese Population

Abstract: Objective: We aimed to investigate the relationships of body mass index (BMI), waist circumference (WC), and obesity defined using a combination of both indexes, with the incidence of hypertension in a Chinese community-based population. Methods: A total of 1,927 Chinese participants (57.2 ± 8.9 years old) with normal blood pressure at baseline were recruited from the Shijingshan community in Beijing. Incident hypertension was defined as blood pressure ≥140/90 mm Hg, self-reported hypertension, or the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
23
0
2
Order By: Relevance
“…There is a clear link between obesity and hypertension [ 9 11 ]. Specifically, increases in weight, body mass index (BMI), WC, waist-to-hip ratio (WHR), and waist-to-height ratio were associated with a higher incidence of hypertension [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear link between obesity and hypertension [ 9 11 ]. Specifically, increases in weight, body mass index (BMI), WC, waist-to-hip ratio (WHR), and waist-to-height ratio were associated with a higher incidence of hypertension [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At least 2.8 million and 17.9 million people die each year due to overweight or obesity and from CVD, respectively [5,8]. There is a clear link between obesity and hypertension [9][10][11]. Specifically, increases in weight, body mass index (BMI), WC, waistto-hip ratio (WHR), and waist-to-height ratio were associated with a higher incidence of hypertension [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian ini tidak didapatkan hubungan yang bermakna antara lpi dengan tekanan darah sistolik dan diastolik, namun didapatkan prevalensi rasio subjek dengan lpi berlebih sebesar 1,73 kali untuk mengalami hipertensi dibandingkan subjek dengan Lpi dalam batas normal. Hasil ini sesuai dengan penelitian yang telah dilakukan bahwa lpi dapat digunakan sebagai prediksi kejadian hipertensi (Momin, 2020).…”
Section: Hubungan Status Gizi Dan Lingkar Pinggang Dengan Hipertensiunclassified
“…Some of the associations of parameters observed within F1 are well known. Numerous studies have shown that overall obesity, defined by BMI (overall obesity) or WC (central obesity) is associated with hypertension [30,31]. Hypertension has been closely associated with obesity-related parameters not only in adults but also in adolescents, so that normal weight and overweight have shown a positive association with healthy and high BP, respectively [32].…”
Section: Factor Analysismentioning
confidence: 99%